A NEW SPECTRUM DEVELOPMENT METHODOLOGY FOR ACCELERATED DURABILITY TEST - YU JiaWei; ZHENG SongLin; ZHAO ZiShun; DONG YuanMing; JIANG ShangJun (Jixie qiangdu)
Loading spectrum acquired from proving ground contains a large percentage of low-amplitude loads. For accelerated durability test spectrum development,many small load omission criterions（ SLOC） have been induced. However,only the damage effect of low-amplitude loads was considered. The strengthening effect was ignored in the traditional SLOCs. A new SLOC was induced by considering the strengthening effect. This criterion was applied to develop target spectrum of a certain load section from proving ground,and an accelerated spectrum was created. To verify the validness of this methodology,analyses of original spectrum and the accelerated spectrum were conducted from multi-aspects,including amplitude domain（ level crossing counting and rain-flow counting）,damage domain（ damage reservation and rain-flow cycle damage distribution）,and frequency domain（ shock response spectrum and fatigue damage spectrum）. The results show that the accelerated spectrum has reserved spectrum damage,guaranteed damage distribution characteristics and frequency characteristics. Finally,vehicle bench iteration test was conducted,and results show that original spectrum can be replaced by the accelerated spectrum as the durability test spectrum. The validness of this methodology has been demonstrated.